Linguistic and Cultural Analysis of the Treaty between Germany and France - Faizullina, Rushana A.; Ivanova, Tatiana K.; Matoushevskaya, Galina V. (Journal of History Culture and Art Research, 2019)
The study deals with structuring of the analysis of the politically orientated texts in order to identify the main ideological content at the linguistic level and its expression in the text. In the course of the research, the influence of linguistic and spatial-social factors is revealed. The linguistic expression of the content changes depending on the purposes of communication and the social group in which it is currently taking place. The lexical units in these texts are inextricably linked with the associative field of this culture carriers. The analysis of a political text conducted without taking into account these specifics will be incomplete. It can lead to distortion of the original meaning and misunderstanding. The study develops the criteria for linguistic objectification of the text ideological orientation. To confirm the objectivity of the information received the linguistic analysis of the politically orientated texts is carried out. The treaty between Germany and France concluded in 2019 in Aachen is under consideration. Its analysis specifies the implementation sequence of separate stages of the analysis of the political text taking into account its specifics and outlines the content of the politically oriented texts according to the scheme offered by the authors of the research.